Comparison of short-term recovery in children with obstructive sleep apnea undergoing tonsillotomy vs. tonsillectomy - Dang, Yanwei; Li, Yujie; Zhang, Junbo; Huang, Wei; Dong, Yuke; Shen, Xiao; Han, Wei; Li, Tao (Frontiers in Pediatrics, 2022)
Objectives: To compare the pain levels, degrees of pharyngeal swelling, and weight loss after tonsillectomy vs tonsillotomy in children clinically diagnosed with obstructive sleep apnea (OSA) over the first seven postoperative days,and to determine which procedure was associated with better recovery in the early postoperative period.Methods: Between April 2021 and December 2021, 121 children with OSA (80 males and 41 females), ranging from 3 to 12 years of age with an average age of 6.7 years, were prospectively enrolled in this study conducted at Zhengzhou Central Hospital Affiliated to Zhengzhou University. The patients were randomly divided into two groups: a tonsillotomy group with 63 cases (40 males and 23 females) and a tonsillectomy group with 58 cases (40 males and 18 females). The patients’ pain levels (as indicated by Parents’ Postoperative Pain Measure [PPPM] scores) and degrees of pharyngeal swelling were recorded for seven days postoperatively, and the patients’ body weights were recorded on postoperative day seven.Results: In the tonsillotomy group, the PPPM scores were the highest on the day of surgery and on the first postoperative day; the patients’ pain levels gradually decreased.The PPPM scores in the tonsillectomy group were higher than those in the tonsillotomy group from the day of surgery to the seventh postoperative day (p < 0.05). The degree of pharyngeal swelling was lower in the tonsillotomy group than in the tonsillectomy group. Weight loss was lower in the tonsillotomy group than in tonsillectomy group on the 7th day after surgery (p < 0.05). On the fifth, sixth, and seventh postoperative days, compared with preschool children, school-age children who had undergone tonsillotomy experienced more pain relief than those who had undergone tonsillectomy (p < 0.05). Conclusion: Children with OSA experienced less pain, less pharyngeal swelling, and less weight loss with tonsillotomy than with tonsillectomy. On the fifth, sixth, and seventh postoperative days,compared with preschool children, tonsillotomy in school-age children is more advantageous in school-age children.